2019
DOI: 10.1016/j.ijhydene.2019.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Microkinetic modelling and reaction pathway analysis of the steam reforming of ethanol over Ni/SiO2

Abstract: Hydrogen production via the steam reforming of biomass-derived ethanol is a promising environmental alternative to the use of fossil fuels and a means of clean power generation. A microkinetic modelling study of ethanol steam reforming (ESR) on Nickel is presented for the first time and validated with minimal parameter fitting against experimental data collected over a Ni/SiO2 catalyst. The thermodynamically consistent model utilises Transition State Theory and the UBI-QEP method for the determination of kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…This is more noticeable on the TOF plot (Figure 5c), where a clearly negative reaction order in respect to water is obtained for the latter catalysts, whereas on the ceria containing ones the slope is still negative but much closer to zero. Various studies, including our previous work on Ni/SiO2 [25], have suggested that a negative partial reaction order for steam indicates the competitive adsorption of ethanol and water for the same active sites, with the metal surface being gradually saturated by adsorbed water species [63,64]. Clearly, the high oxygen mobility and large oxygen storage capacity of CeO2 allows for an efficient dissociation of steam across its entire surface and a fast delivery of O species to the metal that prevents to a large degree the latter's saturation by steam, as carbon-containing surface intermediates are effectively oxidised.…”
Section: Variation Of Water Partial Pressurementioning
confidence: 99%
“…This is more noticeable on the TOF plot (Figure 5c), where a clearly negative reaction order in respect to water is obtained for the latter catalysts, whereas on the ceria containing ones the slope is still negative but much closer to zero. Various studies, including our previous work on Ni/SiO2 [25], have suggested that a negative partial reaction order for steam indicates the competitive adsorption of ethanol and water for the same active sites, with the metal surface being gradually saturated by adsorbed water species [63,64]. Clearly, the high oxygen mobility and large oxygen storage capacity of CeO2 allows for an efficient dissociation of steam across its entire surface and a fast delivery of O species to the metal that prevents to a large degree the latter's saturation by steam, as carbon-containing surface intermediates are effectively oxidised.…”
Section: Variation Of Water Partial Pressurementioning
confidence: 99%
“…The reaction pathways and the side reactions of ESR have been well discussed in several books and reviews , . The main point of designing good catalysts is to enhance the main reactions in the ESR as mentioned in the Introduction, while avoiding the side reactions including ethanol dehydration, reverse water‐gas shift reaction, methanation, and deposition of carbon species as follows: true normalC5 normalOH normalC4 + normalH2 normalO true normalCO2 + normalH2 normalCO+ normalH2 normalO truenormalCO+3 normalH2 normalCH4 + normalH2 normalO true normalCO2 +4 normalH2 normalCH4 +2 normalH2 normalO true2normalCO normalCO2 +normalC …”
Section: Discussionmentioning
confidence: 99%
“…The reaction pathways and the side reactions of ESR have been well discussed in several books and reviews [89,[137][138][139][140]. The main point of designing good catalysts is to enhance the main reactions in the ESR as mentioned in the Introduction, while avoiding the side reactions including ethanol dehydration, reverse water-gas shift reaction, methanation, and deposition of carbon species as follows:…”
Section: Discussionmentioning
confidence: 99%
“…CO and H 2 are mainly produced with low water input, while CO 2 and H 2 are mainly produced by high water input. Despite the apparent simplicity of these two reactions, complex simultaneous reactions of ethanol decomposition (Equation (3)), methane steam reforming (Equations (4) and (6)), and water-gas shift (Equation (5)) can occur [14,17]. The heat needed for ethanol steam reforming can be obtained from fuel combustion out of the reaction tube.…”
Section: Modeling and Simulationmentioning
confidence: 99%
“…Roychowdhury et al [13] modeled the heat transfer of the ethanol steam-reforming process in a microchannel reactor, which found that the conversion rate can be reached as high as 100% when flue-gas flowing supplies the necessary heat. Afolabi et al [14] established a microkinetic model of ethanol steam reforming over a nickel catalyst, which can correctly describe experimental trends. New concepts of self-sustained electrochemical promotion catalysts for partial oxidation of heavy hydrocarbons were also proposed in References [5,15].…”
Section: Introductionmentioning
confidence: 99%